Dose-response analysis of effects of antibodies to large ganglion cells on the cat's retinogeniculate pathways - Crabtree, JW (J Neurosci, 1986)
Previous studies have shown that antibodies against large retinal ganglion cells (alpha-/Y-cells) reduce the Y-cell retinogeniculate pathway while having little or no effect on the X- or W-cell pathways. The present study investigated the dose-response relationship of these effects. We began by studying effects on the T1 (largely Y-cell- mediated) and T2 (largely X-cell-mediated) waves of the retinal field- potential. Different concentrations of the antibodies were injected intraocularly in adult cats and retinal field-potentials evoked by optic chiasm stimulation were examined. The lowest concentration of immune serum tested (330 micrograms/100 microliter volume) reduced both the T1 and T2 amplitudes. With increasing concentrations, the ratio of T1:T2 amplitudes progressively decreased from 0.71 to only 0.05. The highest concentration of immune serum tested (1000 micrograms/100 microliter volume) virtually eliminated the T1 wave while the T2 wave remained (albeit reduced). Next, we carried out single-cell physiological and morphological studies to verify the effects of the highest antibody concentration and compare them with previous results on effects of the lowest antibody concentration (Kornguth et al., 1982; Spear et al., 1982). In single-cell recordings from the retina, the encounter rates of Y- and X-cells were reduced by 85 and 53%, respectively, after injection of the highest antibody concentration. There was no effect on the encounter rate of retinal W-cells. After injection of the lowest antibody concentration, there was no change in the encounter rates of any of the retinal cell types. Morphological studies revealed an 88–99% loss of alpha-cells in retinae treated with the highest antibody concentration. There also was a substantial (24– 57%) loss of medium-size ganglion cells but no loss of small ganglion cells. The loss of alpha-cells was much greater after high- concentration injections than after low-concentration injections. In recordings from the LGN, the proportion of Y-cells was reduced by 87% in laminae receiving input from an eye injected with the highest antibody concentration. Laminae receiving input from an eye injected with the lowest concentration had a 77% reduction in Y-cells. The encounter rate of LGN X-cells was not affected by either concentration. Morphological analysis indicated that the loss of Y-cells in the LGN was not due to changes in cell size. These findings indicate that antibody-mediated effects on retinogeniculate pathways are dose- dependent.(ABSTRACT TRUNCATED AT 400 WORDS)